The Effect of Anterior Uterocervical Angle on Primary Dysmenorrhea and Disease Severity - Mefkure Eraslan Sahin; Erdem Sahin; Yusuf Madendag; Ilknur Col Madendag; Ahter Tanay Tayyar; Fatma Özdemir; Gokhan Acmaz; Iptisam Ipek Muderris (Pain Research and Management)
Background. Primary dysmenorrhea, defined as painful menstrual cramps originating in the uterus without underlying pathology, is a gynecological disease that affects quality of life and school success. Our goal was to determine the effect of anterior uterocervical angle on primary dysmenorrhea and disease severity. Methods. A total of 200 virgin adolescents, 16 to 20 years of age, were included in the study. The Andersch and Milsom scale was used to determine dysmenorrhea severity. Those with pathologies causing secondary dysmenorrhea were excluded from the study. Study subjects were grouped based on severity of pain. Demographic characteristics and uterocervical ultrasonographic measurements were compared among groups. Results. Of the 200 participants enrolled in the study, 50 were healthy controls and 150 had primary dysmenorrhea. Those with primary dysmenorrhea had a significant family history of primary dysmenorrhea compared with controls (P<0.001). Age (P=0.668), body mass index (P=0.898), menarche age (P=0.915), and length of menstrual cycles (P=0.740) were similar in all groups. The uterine corpus longitudinal axis, uterine corpus transverse axis, and uterine cervix longitudinal axis were also similar (P=0.359, P=0.279, and P=0.369, resp.). The mean uterocervical angle was 146.8 ± 6.0 in controls and 143.3 ± 7.3 in those with mild pain with no significant difference between the groups. In those with moderate pain, the mean uterocervical angle was 121.2 ± 7.3 compared with 101 ± 9.2 in those with severe pain, which was a significant difference. Additionally, there was also a significant difference in the uterocervical angle among those with mild, moderate, and severe pain (P<0.001). Conclusion. Our results indicate that a narrower anterior uterocervical angle is associated with primary dysmenorrhea and disease severity.